Placental transfer of NMDAR antibodies causes reversible alterations in mice. Issue 1 (January 2021) - García-Serra, Anna; Radosevic, Marija; Pupak, Anika; Brito, Veronica; Ríos, José; Aguilar, Esther; Maudes, Estibaliz; Ariño, Helena; Spatola, Marianna; Mannara, Francesco; Pedreño, Marta; Joubert, Bastien; et al.
Abstract : Objective: To determine whether maternofetal transfer of NMDA receptor (NMDAR) antibodies has pathogenic effects on the fetus and offspring, we developed a model of placental transfer of antibodies. Methods: Pregnant C57BL/6J mice were administered via tail vein patients' or controls' immunoglobulin G (IgG) on days 14–16 of gestation, when the placenta is able to transport IgG and the immature fetal blood-brain barrier is less restrictive to IgG crossing. Immunohistochemical and DiOlistic (gene gun delivery of fluorescent dye) staining, confocal microscopy, standardized developmental and behavioral tasks, and hippocampal long-term potentiation were used to determine the antibody effects. Results: In brains of fetuses, patients' IgG, but not controls' IgG, bound to NMDAR, causing a decrease in NMDAR clusters and cortical plate thickness. No increase in neonatal mortality was observed, but offspring exposed in utero to patients' IgG had reduced levels of cell-surface and synaptic NMDAR, increased dendritic arborization, decreased density of mature (mushroom-shaped) spines, microglial activation, and thinning of brain cortical layers II–IV with cellular compaction. These animals also had a delay in innate reflexes and eye opening and during follow-up showed depressive-like behavior, deficits in nest building, poor motor coordination, and impaired social-spatial memory and hippocampal plasticity. Remarkably, all these paradigms progressively improved (becoming similar to those of controls) during follow-up until adulthood. Conclusions: In this model, placental transfer of patients' NMDAR antibodies caused severe but reversible synaptic and neurodevelopmental alterations. Reversible antibody effects may contribute to the infrequent and limited number of complications described in children of patients who develop anti-NMDAR encephalitis during pregnancy.